Evaluasi Layanan Perpustakaan Keliling Pada Dinas Kearsipan dan Perpustakaan Kabupaten Badung - Suka Arsana, I Made; Premierita, Ni Putu; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2017)
This research is a descriptive quantitative research that aims to evaluate of mobile library service Badung regency. The independent variable in this research is library service and dependent variable is user satisfaction. The subject of this research is the users of mobile library Badung regency. The study was conducted in April 2017. The total population is 271 users while the total sample is 162 users. The techniques of collecting data with questionnaires distribution, literature study, and observation. The sampling techniques used is Proportionate Random Sampling. The data that which have been processed presented in table form. The results of this research indicates that users feel happy when the mobile library comes, so they suggest that mobile libraries are more often visit their places. The quality of library services affect to the user satisfaction, because if better services are given so user satisfaction increase. Keywords: Mobile Library, Library Service, User Satisfaction